2017
DOI: 10.1080/02670836.2016.1198114
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble fullerenes for medical applications

Abstract: Research on fullerenes occupies a unique position in the scientific arena. Synthesis and characterisation of this nanomaterial blur the line between materials science and chemistry; careful tuning of the processing methods gives birth to a whole family of molecules and their functionalised derivatives, whose unusual properties at this nanoscopic scale can be exploited in cutting-edge technological applications. This review focuses on the functionalisation of fullerenes for use in medical applications. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 143 publications
(303 reference statements)
1
65
0
Order By: Relevance
“…Fullerenol pos sesses antioxidant properties due to its electron deficient sur faces, which are able to attract ROS. [201] Once ROS interacts with fullerenol, an electron transfer takes place that suppresses the oxidant stress caused by ROS. Hao et al tested this hydrogel in a MI rat model and found that the hydrogel appeared to decrease the levels of ROS in this model.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Fullerenol pos sesses antioxidant properties due to its electron deficient sur faces, which are able to attract ROS. [201] Once ROS interacts with fullerenol, an electron transfer takes place that suppresses the oxidant stress caused by ROS. Hao et al tested this hydrogel in a MI rat model and found that the hydrogel appeared to decrease the levels of ROS in this model.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Two-step fabrication of CNOs decorated with Pd nanoparticles using a vortex fluidic device was also reported. [126] First, pretreatment of CNOs with a surfactant such as p-phosphonic acid calix [8]arene was performed. Next, the CNO-calixarene derivatives were mixed with H 2 PdCl 2 in the presence of hydrogen gas.…”
Section: Covalent and Non-covalent Functionalization Of Cnosmentioning
confidence: 99%
“…Non‐modified CNs have poor solubility in organic and inorganic solvents because of aggregation, which is a result of intermolecular interactions such as van der Waals forces . In this context, functionalization is required to improve their solubility and allow their application in multiple fields …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For .25 years, derivatives of this class of NP have served as a platform for a variety of biomedical applications including X-ray and magnetic resonance imaging (MRI) contrast agents, [3][4][5][6] drug delivery, [5][6][7][8][9][10][11][12][13] antioxidant neuroprotection,…”
Section: Introductionmentioning
confidence: 99%